Graphene-filter-mounted tin-oxide-nanowire-transistor for chemical sensor. (5th November 2018) - Kang, Youngsoo; Ju, Sanghyun
Abstract: When attempting to measure the chemical concentration in water using a semiconductor sensor, an abnormal current change occurs when the semiconductor channel is directly exposed to the water containing the chemical substance. To accurately measure the concentration of the chemical substances in the water, it is necessary to cover the semiconductor channel region with a selective filter that allows the chemical vapor to pass through but not the chemical solution and water. In this study, we investigated a method for detecting chemical substances present in water, using a tin oxide (SnO2 ) nanowire transistor incorporated with a three-dimensional (3D)-graphene-based selective filter with (heptadecafluoro-1, 1, 2, 2-tetrahydrodecyl)trichlorosilane (HDF-S), which selectively allowed the chemical vapor to pass through, but blocked the liquid chemical and water. When the chemical vapors, such as nitric acid, toluene, and benzene, in water penetrated the 3D-graphene-based selective filter with HDF-S and contacted the SnO2 nanowire channel, the conductivity of the SnO2 nanowire transistor changed according to the chemical concentration. Thus, the SnO2 nanowire transistor used as a chemical sensor was immersed in water containing chemical substances, to determine the chemical concentration accurately.